Comprehensive Insights Into Pediatric Craniopharyngioma: Endocrine and Metabolic Profiles, Treatment Challenges, and Long-term Outcomes from a Multicenter Study - Zeynep Şıklar; Elif Özsu; Sirmen Kızılcan Çetin; Samim Özen; Filiz Çizmecioğlu-jones; Hanife Gül Balkı; Zehra Aycan; Damla Gökşen; Fatih Kilci; Sema Nilay Abseyi; Ummahan Tercan; Gözde Gürpınar; et al. (Galenos Yayincilik, 2024)
INTRODUCTION: Craniopharyngiomas (CPG) have complex treatment challenges due to their proximity to vital structures, surgical and radiotherapeutic complexities, and the tendency for recurrence. The aim of this study was to identify the prevalence of endocrine and metabolic comorbidities observed during initial diagnosis and long-term follow-up in a nationwide cohort of pediatric CPG patients. A further aim was to highlight the difficulties associated with CPG management. METHODS: Sixteen centers entered CPG patients into the ÇEDD NET data system. The clinical and laboratory characteristics at presentation, administered treatments, accompanying endocrine, metabolic, and other system involvements, and the patient's follow-up features were evaluated. RESULTS: Of the 152 evaluated patients, 64 (42.1%) were female. At presentation, the mean age was 9.1±3.67, ranging from 1.46 to 16.92, years. The most common complaints at presentation were headache (68.4%), vision problems (42%), short stature (15%), and nausea and vomiting (7%). The surgical procedures were gross total resection (GTR) in 97 (63.8%) and subtotal resection in 55 (36.2%). Radiotherapy (RT) was initiated in 11.8% of the patients. Histopathological examination reported 92% were adamantinamatous type and 8% were papillary type. Postoperatively, hormone abnormalities consisted of thyroid-stimulating hormone (92.1%), adrenocorticotropic hormone (81%), antidiuretic hormone (79%), growth hormone (65.1%), and gonadotropin (43.4%) deficiencies. Recombinant growth hormone treatment (rhGH) was initiated in 27 (17.8%). The study showed hesitancy among physicians regarding rhGH. The median survival without relapse was 2.2 years. Median (range) time of relapse was 1.82 (0.13-10.35) years. Relapse was related to longer followups and reduced GTR rates. The median follow-up time was 3.13 years. Among the last follow-up visits, the prevalence of obesity was 38%, but of these, 46.5% were already obese at diagnosis. However, 20% who were not obese at baseline became obese on follow-up. Permanent visual impairment was observed in 26 (17.1%), neurological deficits in 13 (8.5%) and diabetes mellitus in 5 (3.3%) patients. DISCUSSION AND CONCLUSION: Recurrence was predominantly due to incomplete resection and the low rate of postoperative RT. Challenges emerged for multidisciplinary regular follow ups. It is suggested that early interventions, such as dietary restrictions and increased exercise to prevent obesity, be implemented.